RETRACTED: In Vivo Clearance of Apoptotic Debris From Tumor Xenografts Exposed to Chemically Modified Tetrac: Is There a Role for Thyroid Hormone Analogues in Efferocytosis? - Godugu, Kavitha; Mousa, Shaker A.; Glinsky, Gennadi V.; Lin, Hung-Yun; Davis, Paul J. (Frontiers in Endocrinology, 2022)
Apoptosis is induced in cancer cells and tumor xenografts by the thyroid hormone analogue tetrac or chemically modified forms of tetrac. The effect is initiated at a hormone receptor on the extracellular domain of plasma membrane integrin αvβ3. The tumor response to tetrac includes 80% reduction in size of xenograft, e.g., glioblastoma, in two weeks of treatment, with absence of residual apoptotic cancer cell debris; this is consistent with efferocytosis. The molecular basis for efferocytosis linked to tetrac is incompletely understood, but several factors are proposed to play roles. Tetrac-based anticancer agents are pro-apoptotic by multiple intrinsic and extrinsic pathways and differential effects on specific gene expression, e.g., downregulation of the X-linked inhibitor of apoptosis (XIAP) gene and upregulation of pro-apoptotic chemokine gene, CXCL10. Tetrac also enhances transcription of chemokine CXCR4, which is relevant to macrophage function. Tetrac may locally control the conformation of phagocyte plasma membrane integrin αvβ3; this is a cell surface recognition system for apoptotic debris that contains phagocytosis signals. How tetrac may facilitate the catabolism of the engulfed apoptotic cell debris requires additional investigation.